1H MRS in the human spinal cord at 7 T using a dielectric waveguide transmitter, RF shimming and a high density receive array. (18th May 2016) - Henning, A.; Koning, W.; Fuchs, A.; Raaijmakers, A.; Bluemink, J. J.; van den Berg, C. A. T.; Boer, V. O.; Klomp, D. W. J.
Abstract : Multimodal MRI is the state of the art method for clinical diagnostics and therapy monitoring of the spinal cord, with MRS being an emerging modality that has the potential to detect relevant changes of the spinal cord tissue at an earlier stage and to enhance specificity. Methodological challenges related to the small dimensions and deep location of the human spinal cord inside the human body, field fluctuations due to respiratory motion, susceptibility differences to adjacent tissue such as vertebras and pulsatile flow of the cerebrospinal fluid hinder the clinical application of 1 H MRS to the human spinal cord. Complementary to previous studies that partly addressed these problems, this work aims at enhancing the signal‐to‐noise ratio (SNR) of 1 H MRS in the human spinal cord. To this end a flexible tight fit high density receiver array and ultra‐high field strength (7 T) were combined. A dielectric waveguide and dipole antenna transmission coil allowed for dual channel RF shimming, focusing the RF field in the spinal cord, and an inner‐volume saturated semi‐LASER sequence was used for robust localization in the presence of B 1 + inhomogeneity. Herein we report the first 7 T spinal cord 1 H MR spectra, which were obtained in seven independent measurements of 128 averages each in three healthy volunteers. The spectra exhibit high quality (full width at half maximum 0.09 ppm, SNR 7.6) and absence of artifacts and allow for reliable quantification of N‐acetyl aspartate (NAA) (NAA/Cr (creatine) 1.31 ± 0.20; Cramér–Rao lower bound (CRLB) 5), total choline containing compounds (Cho) (Cho/Cr 0.32 ± 0.07; CRLB 7), Cr (CRLB 5) and myo‐inositol (mI) (mI/Cr 1.08 ± 0.22; CRLB 6) in 7.5 min in the human cervical spinal cord. Thus metabolic information from the spinal cord can be obtained in clinically feasible scan times at 7 T, and its benefit for clinical decision making in spinal cord disorders will be investigated in the future using the presented methodology. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper reports the first 7 T spinal cord 1 H MR spectra. To tackle the B 1 + inhomogeneity during transmission at 7 T a dielectric waveguide and dipole antenna transmission coil, dual channel RF shimming and inner‐volume saturated sLASER were combined. A tight fit 30‐channel receive array enabled optimal SNR. Quantitative results from seven independent scans were obtained and compared with previous 3 T results.